Hedonic Experience and Behavioral Control as Predictors of Mobile Banking Continuance: Empirical Evidence from BRImo Users in Indonesia - Hamdani Hamdani; Noor Emiliani Putri; ST Nurhasanah; Andi Nurhasanah; Andi Syarifuddin; Syachrul Syachrul (Asian Journal of Environmental Research, 2025)
Mobile banking has become one of the most transformative innovations in the financial technology landscape, yet sustaining users' continuance intention remains a major challenge for digital banking providers. This study aims to analyze the influence of perceived enjoyment and behavioural control on users' continuance intention to use BRImo, a leading mobile banking application in Indonesia. Employing a quantitative explanatory design, data were collected from 100 BRImo users in Samarinda using a structured Likert-scale questionnaire distributed both offline and online. The instrument passed validity and reliability testing, and data were analyzed using multiple linear regression, accompanied by t-tests, F-tests, and R² evaluation. The findings indicate that both perceived enjoyment and behavioural control exert a positive and significant effect on continuance intention (β = 0.346; p = 0.002 and β = 0.404; p = 0.000, respectively). The simultaneous influence of the two variables was confirmed through the F-test (F = 76.190; p < 0.001). The model demonstrates strong explanatory power, with an R² value of 0.603, indicating that the two predictors explain 60.3% of users' continuance intention, while the remaining 39.7% may be attributed to variables such as trust, satisfaction, habit, and service quality. These results highlight the critical roles of hedonic experience and perceived behavioural control in shaping post-adoption behaviour in mobile banking services. The study extends the applicability of TAM and TPB in a post-adoption context and provides practical implications for digital banking providers to enhance user experience, emotional engagement, and perceived control to strengthen long-term usage.